"The Struggle is Real": Punitive assessment in community services. (July 2022) - Quirouette, Marianne
Assessment tools are pivotal for the work of frontline community services providers, shaping client relationships, access to supports and producing evidence for agencies that need to allocate resources, demonstrate outcomes and secure funding. These tools are combined and used cumulatively, as marginalized individuals are cared for – but also controlled and punished - within these systems (e.g. in shelters, street outreach, mental health or re entry supports). Punishment literature has clarified that risk tools are impactful but also contested and resisted. Still, we know little about how the process is experienced and negotiated by frontline by practitioners working with people pushed through the 'revolving doors'. Drawing from two years of ethnographic fieldwork and 105 interviews with community practitioners, I examine tools and practices used to 'assess' criminalized and marginalized individuals. I show that practitioners are producing evidence about problems occurring outside legal institutions while relying on criminal justice logics and engaging with criminal justice spaces and paces. I highlight the challenges service providers face and negotiate, focusing on three themes: the composition of tools, the process of using them, and the service context in which they are used. I argue that despite discretionary efforts and adaptations, community practitioners remain frustrated by assessment tools and practices, and particularly by their inability to meet the needs they are assessing.